A REVIEW ON SECURITY ENHANCEMENT THROUGH ANONYMOUS ROUTING IN MANET - SR, DRISHYA; Vijayakumar, Vaidehi (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Mobile Ad Hoc Network(MANET) is an infrastructure less network. Any node may enter or leave network at anytime. MANET also has less resources and limited security. MANET is vulnerable to attacks because of its lack of centralized infrastructure. Security in MANET can be achieved by Anonymous routing which hide source, destinationand route information to provide. This paper provides a review on efficient anonymous routing protocols used in MANET and also compares the security in terms of identity, location and route anonymity. An anonymous routing protocol that conceals the essential details and satisfies the basic protocol properties has to be proposed.